APPLICATION OF THE HIRARC METHOD TO ASSESS HOME ENVIRONMENTAL HAZARDS AMONG ELDERLY: THE ROLE OF FUNCTIONAL INDEPENDENCE AND NUTRITIONAL STATUS - Riza Irianingtyas; Widya Nurcahyaningtyas; Nima Eka Nur Rahmania; Esa Risqianti Yana; Salsabila Nur A’yuni Nugraha Putri (Nurse and Health: Jurnal Keperawatan, 2026)
Background: The increasing elderly population is associated with an increased risk of injury due to declining physical function and hazards within the home environment. Home safety is influenced by both environmental and individual factors, including independence level and nutritional status. The Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method can be used to identify and assess home environmental hazards systematically Purpose: This study aimed to analyze the relationship between independence level and nutritional status with home environmental hazard levels among older adults based on the HIRARC method. Methods: A cross-sectional analytical study was conducted among 30 alderly selected through total sampling. Independence level was measured using the Barthel Index, nutritional status was assessed using Body Mass Index (BMI), and home environmental hazards were evaluated using the HIRARC method. Data were analyzed using descriptive statistics and Spearman rank correlation tests with a significance level of 0.05. Results: Most respondents were female (56.7%) and aged 60–69 years (66.7%). Nearly half had normal nutritional status (46.7%) and were categorized as independent (46.7%). Home hazard assessment indicated that 53.3% of homes were at moderate risk. The most common hazards were slippery bathroom floors (60.0%), inadequate lighting (46.7%), and the absence of handrails (40.0%). Significant relationships were found between independence level and home environmental hazards (p=0.004), between nutritional status and home environmental hazards (p=0.028) Conclusion: Independence level and nutritional status are significantly associated with home environmental hazard levels among elderly. Improving home safety, maintaining functional independence, and promoting optimal nutritional status are important strategies to prevent injuries and support healthy aging